Locus of control, financial knowledge, financial attitude, financial self-efficacy, and social economic status as antecedents of financial management behavior - Rahmawati, Umi; Marcella, Eka (Journal of Management and Business Insight, 2023)
Purpose-This study aims to investigate past trends in financial management practices. Factors such as locus of control, financial literacy, financial mindset, financial self-efficacy, and socioeconomic standing are thought to influence financial management practices. Design/Methodology/Approach-In this study, a sample of 92 students from the Faculty of Economics and Business in the Daerah Istimewa Yogyakarta who responded to questionnaires as part of a quantitative approach to data collection. Purposive sampling is the sampling method employed, and the Likert scale is the scale measurement instrument. Using the SPSS analysis tool, multiple linear regression analysis is used to test hypotheses. Findings-All factors assumed to influence financial management behavior were shown to be advantageous, according to the study's findings. Evidence has shown that locus of control, financial knowledge, financial attitude, financial self-efficacy, and social economic standing positively influence the financial management behavior of students at the Faculty of Economics and Business in the Daerah Istimewa Yogyakarta. Research limitations/implications-The results of the research are expected to serve as a guide and a source of knowledge for everyone, particularly for children and students who are trying to develop or maintain good money management habits. This study found that a variety of factors, including locus of control, financial knowledge, financial attitude, financial self-control, and social economic status, can influence a person's financial management behavior. Originality/value-There is currently a dearth of research on students in Daerah Istimewa Yogyakarta who practice sound financial management. This study aims to identify the variables influencing the financial management practices of Daerah Istimewa Yogyakarta students enrolled in the Faculty of Economics and Business.